2019
DOI: 10.1111/jcmm.14212
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA‐205 is associated with diabetes mellitus‐induced erectile dysfunction via down‐regulating the androgen receptor

Abstract: As a major class of regulatory genes in majority metazoans, microRNAs (miRs) play an important role in various diseases including diabetes mellitus (DM). Lack of androgens has previously been associated with DM‐induced erectile dysfunction (DMED). In addition, the biological functioning of androgen is mediated by androgen receptor (AR). Herein, we sought to investigate whether miRs participate in AR‐associated DMED. Sprague‐Dawlay rats were employed to establish DMED models. After modelling, levels of miR‐205 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…Exogenous overexpression of miR-205 in mouse granulosa cells promoted apoptosis and increased caspase-3/9 activity. The expression of miR-205 was increased in rat cavernous smooth muscle cells, which inhibited cell proliferation and promoted apoptosis by targeting AR (Wen et al, 2019). Taking those studies and ours together, miR-205 plays a role in promoting apoptosis.…”
Section: Discussionsupporting
confidence: 53%
“…Exogenous overexpression of miR-205 in mouse granulosa cells promoted apoptosis and increased caspase-3/9 activity. The expression of miR-205 was increased in rat cavernous smooth muscle cells, which inhibited cell proliferation and promoted apoptosis by targeting AR (Wen et al, 2019). Taking those studies and ours together, miR-205 plays a role in promoting apoptosis.…”
Section: Discussionsupporting
confidence: 53%
“…15 Another study showed that miR-205 is associated with the progression of DMED. 16 In addition, decreased expression of miR-141 is associated with up-regulation of the RhoA/ROCK pathway in DMED rats. 17 These studies together demonstrate that miR-NAs may be up-or downregulated in DMED, therefore modulating the severity of DMED.…”
Section: Introductionmentioning
confidence: 98%
“…Erectile dysfunction (ED) is characterized by the distinctive inability to achieve or maintain a sufficient erectile function for satisfaction during sexual activity [1], which was also accompanied by hypertension, coronary atherosclerosis, and diabetes mellitus [2]. ED is also known as impotency in men, estimated on 322 million men would suffer from ED global by the year 2025 [3], threatening human health, spousal relationship, and family life.…”
Section: Introductionmentioning
confidence: 99%